PENGARUH CAPITAL INTENSITY RATIO, LEVERAGE PERUSAHAAN TERHADAP MANAJEMEN PAJAK DENGAN PROFITABILITAS SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2014-2017 - Eling Ri Kurniati (Sekolah Tinggi Ilmu Ekonomi Tamansiswa Banjarnegara, 2020)
ABSTRACT This research problem is the number of companies that carry out tax management by minimizing the tax burden. The research aims to examine the effect of capital intensive ratio, company leverage on tax management with profitability as an intervening variable. This research was conducted on the Indonesia Stock Exchange (IDX) for the period 2014 to 2017. This study used quantitative research methods. The data used in the study was secondary data. The population in the study were the manufacturing companies listed on the Indonesia Stock Exchange for the period 2014-2017. The sample selected by using the purposive sampling method. The total sample used in this study amounted to 69 manufacturing companies. The analytical method used in this study was analyzing the path that processed with SPSS. The results of this study indicated that the capital intenence ratio, company leverage and profitability were unable to prove the influence of tax management, capital intenstency ratio did not affect profitability, company leverage had a significant effect on profitability. In the intervening profitability variable, was unable to prove the influence of capital intenstance ratios on tax management while profitability was able to mediate the influence of corporate leverage on tax management.